VITALITAS BAHASA DAYAK LINOH DI PEMUKIMAN TRANSMIGRASI JAWA, KECAMATAN SUNGAI TEBELIAN KABUPATEN SINTANG - Siti Maryam; Hotma Simanjuntak; Ahmad Rabi’ul Muzammil (Universitas Tanjungpura, 2021)
AbstractThis research was motivated by the desire to know the vitality of the Linoh Dayak language in Javanese transmigration settlements, Sungai Tebelian District, Sintang Regency. The formulation of the problem in this study is how language skills (listening, speaking, reading, and writing), the choice of the Linoh Dayak community language based on realms (family, neighbors, association, transactions, work, religion, and education), language attitudes Linoh Dayak speakers, and also the implications of research on language learning in schools. This research uses a descriptive method. The results showed that the vitality of the Dayak Linoh language is still safe. The language skills of the people from generation to generation are very good, namely the ability of respondents to master the Linoh Dayak language is above 75%. The language selection of respondents also tends to use Indonesian in several domains. In the family realm, respondents have also started using Indonesian in certain contexts such as talking to their grandchildren, in-laws, and in-laws. The language attitude that the respondents showed was very good. However, the environment which is the area of Javanese transmigration and more Javanese than the Dayak Linoh people, so the use of the Dayak Linoh language is very limited.Keyword: Dayak Linoh, Javanese Transmigration settlement, Language Vitality, Sociolinguistic